Die Energieregion Ruhrgebiet Eine historisch-statistische Studie - Bleidick, Dietmar (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Despite the cessation of coal mining in 2018, the Ruhr area continues to be of considerable importance for the German energy supply. The study uses statistical data to discuss the development since the mid-19th century. The focus is on the historical energy turns triggered by coal, electricity supply, oil and natural gas and the associated processes of change. Another focus, also with topical relevance, is on the nearly one hundred years of experience in the hydrogen economy as the basis of the chemical industry. Thus, for the first time, it offers a synthesis of the diverse energy-economic relationships within the region.